The burden and cost of sickness absenteeism amongst healthcare workers at a teaching hospital in South Africa. A cross-sectional study. - Khan, Muhamed Adil (Department of Public Health and Family Medicine, 2023)
A high burden of sickness-related absenteeism (SRA) amongst healthcare workers (HCWs) may impact health service delivery. The burden is known in high-income settings but not well evaluated in low and middle income (LMIC) settings and absent within a South African context. To determine the prevalence, associated medical conditions and cost of SRA amongst HCWs in a LMIC setting, we evaluated Human Resource (HR) absence records from a teaching hospital in South Africa over a 3 year period. Of the 3,543 HCW employed during the study period, 78% (n = 2,748) had at least 1 SRA episode. The overall SRA prevalence was 2.63%. The mean duration of absence was 2.25 days per episode and the mean frequency was 2.65 episodes per annum. Conditions of the musculoskeletal system (40.1%) were the most commonly reported, followed by acute infections of the upper respiratory tract (13.2%) and other respiratory conditions (6.2%). The total direct cost SRA was US$5,105,061.78 over the study period and the mean direct SRA cost per person was US$1,857.74 per episode. The results demonstrate a higher SRA burden compared with studies in similar settings and prompts further research into the causative factors and targeted risk mitigation strategies.